Passive Design Techniques Applied to Vernacular Housing in Chazuta (Journal SCIENCEVOLUTION, 2025)
Vernacular housing refers to constructions that, through passive architecture, utilize local materials to promote sustainability and safeguard cultural heritage and ancestral knowledge. The objective of this study was to analyze the passive architectural strategies present in vernacular houses in Chazuta, San Martín, Peru, emphasizing how climatic conditions influence construction techniques. The study employed a qualitative, narrative literature review design, including the selection of scientific literature from 31 sources across academic databases such as Scopus, Web of Science, SciELO, and Google Scholar. The findings indicate that passive architectural strategies are effective across various climatic and cultural contexts. In Chazuta, San Martín, Peru, materials such as adobe and thatch are used to enhance thermal insulation, solar orientation, and cross ventilation. These strategies reflect an evolution of passive architecture in the design of local sustainable housing and demonstrate that Chazuta, as a model of architectural revaluation in the Amazon, has revived the use of traditional construction techniques that respond to climate adaptation, promoting comfortable, sustainable, and resilient living spaces.
Keywords: Vernacular Housing; Passive Architecture; Sustainability; Thermal Comfort; Climatic Adaptation